Analisis Faktor-Faktor yang Mempengaruhi Akuntabilitas Pengelolaan BUMDes: Studi di BUMDes Kecamatan Bulango Timur - Kezia Rozalin Kasman; Zulkifli Bokiu; Nurharyati Panigoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the accountability of the management of Village-Owned Enterprises (BUMDes) in East Bulango District through the influence of the internal control system, transparency, human resource competence, and the role of village heads. This study uses a quantitative descriptive and causality approach with primary data collected through the distribution of questionnaires to BUMDes managers. Data analysis was carried out to test the influence of each independent variable partially or simultaneously on the accountability of BUMDes management. The findings of this research are expected to contribute to improving more accountable governance of BUMDes, through strengthening aspects of internal control, transparency, improving human resource competence, and optimizing the role of village heads.